2018
DOI: 10.1007/s40588-018-0107-9
|View full text |Cite
|
Sign up to set email alerts
|

The Cryptococcus neoformans Titan Cell: From In Vivo Phenomenon to In Vitro Model

Abstract: Purpose of Review During infection, the human fungal pathogen Cryptococcus neoformans undergoes an unusual change in size, from small haploid yeast to large polyploid Titan cells. This transition is now well recognized as a virulence factor, but significant questions remain about how Titanisation is regulated and how it influences disease progression. Progress has been impeded by the lack of an in vitro model for the yeast-to-Titan transition, a challenge that was recently overcome by three independent groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 71 publications
(98 reference statements)
0
35
0
Order By: Relevance
“…The example first established by Nielsen and Casadevall benefited not only the PIs on the three papers, but also our teams, particularly graduate students Hommel and Trevijano-Contador, who led the work in the Alanio and Zaragoza labs. We all continue to work in this space, contributing to a broader understanding of the many interacting signals that drive titanization (13). It has also served as an example for others facing similar competitive choices in our field (14)(15)(16)(17).…”
mentioning
confidence: 89%
“…The example first established by Nielsen and Casadevall benefited not only the PIs on the three papers, but also our teams, particularly graduate students Hommel and Trevijano-Contador, who led the work in the Alanio and Zaragoza labs. We all continue to work in this space, contributing to a broader understanding of the many interacting signals that drive titanization (13). It has also served as an example for others facing similar competitive choices in our field (14)(15)(16)(17).…”
mentioning
confidence: 89%
“…Cryptococcosis occurs when desiccated yeast or spores are inhaled, proliferate in the host lung and further disseminate into the central nervous system (2, 3). In response to the earliest interactions with host lung stimuli , C. neoformans cells undergo an unusual morphogenic switch, changing from small haploid yeast to large polyploid titan cells (49). While titan cells are defined as those cells larger than 10 μm in diameters, in vivo they can reach up 50 to 100 μm; typical yeast cells are around 5 μm (4, 5, 10).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, one of the biggest challenges hampering further understanding of the molecular mechanisms driving titanization and their contribution to disease outcome was the lack of an in vitro titan cell induction protocol (10, 15–17). The process of titanization is triggered by environmental stimuli from the host lung, and our group and others have demonstrated that host-relevant stimuli are able to induce titan cells in vitro (9, 15–17). These in vitro generated titan cells exhibited similar features to in vivo induced titan cells, including: enlarged cell sizes, tightly compacted capsule, thicker cell wall, high ploidy and the presence of a single, large vacuole (9, 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of this capsule is highly variable and differs between yeast cells and Titan cells, the latter representing a subset of giant cells (>10 μm in cell body diameter) formed by C. neoformans within the host lung (79). Titan cells contribute to pathogenesis by resisting phagocytosis, enhancing dissemination of yeast to the central nervous system and altering host immune status (7, 913).…”
Section: Introductionmentioning
confidence: 99%